Adenauer and Kennedy a study in German-American relations ; 1961 - 1963 - Mayer, Frank A. (St. Martin's Press, 1996)
German-American relations during the years 1961-1963 were characterized by tension and disagreement as President John F. Kennedy attempted to redefine America's commitment to German reunification, one of the major foreign policy priorities of Chancellor Konrad Adenauer. Frank Mayer focuses on how this process of redefinition affected the Berlin Wall Crisis of 1961-1962. Adenauer and Kennedy also analyzes how Adenauer overcame the hostility displayed by the American government toward the Franco-German Treaty of January 1963, which Adenauer believed was a necessary and historic component of his policy of reconciliation with France. Adenauer and Kennedy demonstrates how the events of this period continue to influence contemporary relations between America and a united Germany. Anyone interested in the current state of German-American relations will want to read this fascinating book.
Keywords: Kennedy, John F., (John Fitzgerald), 1917-1963; Adenauer, Konrad, 1876-1967; Adenauer, Konrad -- 1876-1967; Kennedy, John F. -- 1917-1963; Geschichte 1961-1963; Geschichte; Buitenlandse betrekkingen; Außenbeziehungen; Außenpolitik; Deutsche Frage; Berlinkrise -- 1961; Alemania (República Federal, 1949 1990) - Relaciones exteriores - EE.UU; EE.UU - Relaciones exteriores - 1961 1963; USA; United States -- Foreign relations -- Germany (West); Germany (West) -- Foreign relations -- United States; United States -- Foreign relations -- 1961-1963; Deutschland -- Bundesrepublik